KATA KERJA BAHASA INGGRIS DAN BAHASA TOBELO SUATU ANALISIS KONTRASTIF - BOLANGO, ROKI APOLOS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Â This skripsi is entitled â€œVerbs in English and Tobelo Language: A Contrastive Analysisâ€ The objectives of the research are to identify, classify, and analyze the verbs in English and Tobelo language based on the form, function and meaning; and then find out the similarities and difference according to Ladoâ€™s theory (1957). The theory used in this research, namely, Frank (1972) and arts and arts (1982). The data in English were collected from English Modern books whereas the data of Tobelo language were collected from informants as primary data and the secondary data were collected from internets. English and Tobelo language derived from different language families. English comes from the indo-European Language family. While Tobelo language from west Papuan language family. Therefore, this language have own characteristic. The result of this research showed that verbs in English and Tobelo language had the similarities in kinds of verbs and the differences between English and Tobelo Language of verbs.in English every kind of we have can get it in Tobelo language we have get some kinds of verb Â Key words:Â Verbs in English, Tobelo language and Contrastive Analysis